Analisis Komparatif Literasi Keuangan Bagi Pengelolaan Keuangan Mahasiswa Manajemen Universitas Buana Perjuangan Karawang - Darryl Ammanulloh Sesandi; Sihabuddin; Robby Fauji (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
Students, as the nation's next generation, not only have to face the increasing complexity of goods, services and financial markets, but also have to bear greater financial risks than their parents. College students have greater income and expenses than the population as a whole. Parents should teach their children about money management as many students realize that this does not make them good economic players in today's world. This research is quantitative in nature and t-test for independent samples was used to analyze the data. A total of 192 students participated in this research, both those who were working and those who were not working. Based on the study findings, there is a significant difference for financial literacy and no significant difference for financial management between working and non-working students.